Cryptic diversity and symbiont interactions in rock-posy lichens - Leavitt, Steven D; Kraichak, Ekaphan; Vondrak, Jan; Nelsen, Matthew P; Sohrabi, Mohammad; Perez-Ortega, Sergio; St Clair, Larry L; Lumbsch, H Thorsten (Molecular phylogenetics and evolution, 2016)
Identifying factors that influence species interactions is central to research in symbiotic systems. While lichens represent iconic models of symbiosis and play important roles in understanding the biology of symbiotic interactions, patterns of interactions in lichen symbionts and mechanisms governing these relationships are not well characterized. This is due, in part to the fact that current taxonomic approaches for recognizing diversity in lichen symbionts commonly fail to accurately reflect actual species diversity. In this study, we employed DNA-based approaches to circumscribed candidate species-level lineages in rock-posy lichen symbionts (mycobiont=Rhizoplaca s. lat. species; photobiont=Trebouxia species). Our results revealed a high degree of cryptic diversity in both the myco- and photobionts in these lichens. Using the candidate species circumscribed here, we investigated the specificity of the symbionts toward their partners and inferred the relative importance of various factors influencing symbiont interactions. Distinct mycobiont species complexes, ecozones, and biomes are significantly correlated with the occurrence of photobiont OTUs, indicating that complex interactions among mycobiont lineages, ecogeography, and microhabitat determine interactions between photobionts and their mycobionts in lichen symbiosis. One-to-one specificity between mycobiont and photobiont species was not found, with the exception of R. maheui that associated with a single Trebouxia OTU that was not found with other Rhizoplaca s. lat. species. We estimated the most recent common ancestor of the core Rhizoplaca group at c. 62.5Ma, similar in age to the diverse parmelioid core group in the well-studied family Parmeliaceae. However, in contrast to Parmeliaceae, species in Rhizoplaca were found to associate with a narrow range of photobionts. Our study provides important perspectives into species diversity and interactions in iconic lichen symbiotic systems and establishes a valuable framework for continuing research into rock-posy lichens.
Keywords: DNA fungální; lišejníky; Symbiosis; Lecanoraceae; DNA, Fungal; Specificity; sekvenční analýza DNA; Selectivity; Lichens; Trebouxia; Chlorophyta; biodiverzita; symbióza; Phylogeny; Ecoregion; fylogeneze; Sequence Analysis, DNA; Biodiversity